2013
DOI: 10.1007/s00384-013-1784-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: anal and rectal changes after radiotherapy for prostate cancer

Abstract: Low to moderate quality evidence indicates that EBRT reduces anal resting pressure, decreases rectal distensibility, and frequently induces telangiectasias of rectal mucosa. Objective changes may be associated with fecal incontinence, urgency, frequent bowel movements, and rectal bleeding, but these symptoms are not always related to radiation damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 52 publications
4
41
0
3
Order By: Relevance
“…), all generally point toward detrimental effects of RT on the PFM function. This is in concordance with what was observed by Krol et al [49] in their systematic review on anal and rectal after EBRT for prostate cancer, where decreased anal resting pressure was supported by low to moderate evidence. Lastly, the study by Allgayer et al [28] demonstrated no significant differences in PFM function.…”
Section: Effects Of Rt On the Pfm Functionsupporting
confidence: 93%
“…), all generally point toward detrimental effects of RT on the PFM function. This is in concordance with what was observed by Krol et al [49] in their systematic review on anal and rectal after EBRT for prostate cancer, where decreased anal resting pressure was supported by low to moderate evidence. Lastly, the study by Allgayer et al [28] demonstrated no significant differences in PFM function.…”
Section: Effects Of Rt On the Pfm Functionsupporting
confidence: 93%
“…FI in men who generally have fecal soiling or leakage rather than gross incontinence may be associated with normal sphincteric function 63–67 ; iatrogenic anal injury (eg, after perianal procedures); or dyssynergic defecation, 68 wherein high anal resting pressure entraps feces during defecation and subsequently expels them 69 ; radiation therapy 70 ; or isolated weakness of the internal anal sphincter.…”
Section: F1 Fecal Incontinencementioning
confidence: 99%
“…increased frequency and urgency of defecation, faecal incontinence and rectal bleeding). [22] High dose RT to the rectal wall can lead to anatomical and functional damage including telangectasia, mucosal congestion, ulceration and fibrosis [23] with associated impairment of sensation, compliance and capacity. [24] Similarly, irradiation of the anal sphincter complex may impair function.…”
Section: Radical Therapiesmentioning
confidence: 99%